Informal Labour and Credit Markets : A Survey - Levine, Paul (IMF Working Papers; Working Paper ;, 2010)
This paper reviews the literature on the informal economy, focusing first on empirical findings and then on existing approaches to modeling informality within both partial and general equilibrium environments. We concentrate on labour and credit markets, since these tend to be most affected by informality. The phenomenon is particularly important in emerging and other developing economies, given their high degrees of informal labour and financial services and the implications these have for the effectiveness of macroeconomic policy. We emphasize the need for dynamic general equilibrium (DGE) and ultimately dynamic stochastic general equilibrium (DSGE) models for a full understanding of the costs, benefits and policy implications of informality. The survey shows that the literature on informality is quite patchy, and that there are several unexplored areas left for research.